Proton Gradient Regulation 5-Mediated Cyclic Electron Flow under ATP- or Redox-Limited Conditions: A Study of ƊATPase pgr5 and ƊrbcL pgr5 Mutants in the Green Alga Chlamydomonas reinhardtii. Issue 1 (12th March 2014) - Johnson, Xenie; Steinbeck, Janina; Dent, Rachel M.; Takahashi, Hiroko; Richaud, Pierre; Ozawa, Shin-Ichiro; Houille-Vernes, Laura; Petroutsos, Dimitris; Rappaport, Fabrice; Grossman, Arthur R.; Niyogi, Krishna K.; Hippler, Michael; et al.
Abstract : The Chlamydomonas reinhardtii pgr5 mutant shows photosynthetic and phenotypic traits that support the conservation of PGR5 in both redox-controlled cyclic electron flow and PSI photoprotection . Abstract: The Chlamydomonas reinhardtii proton gradient regulation5 ( Crpgr5 ) mutant shows phenotypic and functional traits similar to mutants in the Arabidopsis ( Arabidopsis thaliana ) ortholog, Atpgr5, providing strong evidence for conservation of PGR5-mediated cyclic electron flow (CEF). Comparing the Crpgr5 mutant with the wild type, we discriminate two pathways for CEF and determine their maximum electron flow rates. The PGR5/proton gradient regulation-like1 (PGRL1) ferredoxin (Fd) pathway, involved in recycling excess reductant to increase ATP synthesis, may be controlled by extreme photosystem I acceptor side limitation or ATP depletion. Here, we show that PGR5/PGRL1-Fd CEF functions in accordance with an ATP/redox control model. In the absence of Rubisco and PGR5, a sustained electron flow is maintained with molecular oxygen instead of carbon dioxide serving as the terminal electron acceptor. When photosynthetic control is decreased, compensatory alternative pathways can take the full load of linear electron flow. In the case of the ATP synthase pgr5 double mutant, a decrease in photosensitivity is observed compared with the single ATPase -less mutant that we assign to a decreased proton motive force. Altogether, our results suggest that PGR5/PGRL1-Fd CEF is most required under conditions when Fd becomes overreduced and photosystem I is subjected to photoinhibition. CEF is not a valve; it only recycles electrons, but in doing so, it generates a proton motive force that controls the rate of photosynthesis. The conditions where the PGR5 pathway is most required may vary in photosynthetic organisms like C. reinhardtii from anoxia to high light to limitations imposed at the level of carbon dioxide fixation.